Is the mazEF toxin-antitoxin system responsible for vancomycin resistance in clinical isolates of Enterococcus faecalis? - Sadeghifard, Nourkhoda; Soheili, Sara; Sekawi, Zamberi; Ghafourian, Sobhan (German Medical Science GMS Publishing House, 2014)
[english] The current study was conducted to investigate the relationship between vancomycin-resistant (VRE) and the presence of toxin-antitoxin (TA) system, which may be useful as target for novel antimicrobial therapy concepts. The susceptibility of was determined by MIC, and the presence of the TA system was evaluated by PCR. Among 200 isolates 39.5% showed resistance to vancomycin (VRE), while 60.5% were susceptible strains (VSE). The TA system was positive in all VRE isolates (100%), but less prevalent (38/121, 31.4%) among the 121 VSE strains. In conclusion, our study demonstrated a positive relationship between the presence of vancomycin resistance and TA system. This observation may introduce therapeutic options against a novel antimicrobial target in enterococci.